Integrated analytic hierarchy process and mixed integer programming for supplier selection in mold and dies industry - Agustinus Silalahi; Ronald Sukwadi; Duhita Al Hayyu Pramesjwari; Chendrasari Wahyu Oktavia; Christine Natalia (Universitas Serang Raya, 2019)
PT. GMT has a mission to deliver the products to the customer on time and high-quality products to improve services. Sometimes, the delivery of product delays caused by the raw materials delays or didn't meet specifications. Selection optimal suppliers of raw materials are one of the solutions. There are two factors must be considered for the selection of suppliers, qualitative factors and quantitative factors. In this study, for qualitative factors, based on the criteria needed by PT GMT. This research produces three Linear Programming models, first: a qualitative objective function that will be maximized called the Total Value of Purchase (TVP). TVP is an integration of the Analytical Hierarchy Process (AHP) and Mix Integer Programming Integration. Second, the quantitative objective function for the procurement cost of raw materials, which is called the Total Cost of Purchase (TCP). The third is to optimize qualitative and quantitative simultaneously using the Goal Programming method. The selection of suppliers based on TVP the total value is 97.25, and the total procurement cost is Rp. 36,914,000, based on TCP, the total value is 89.14, and the total of procurement cost is IDR 31,356,000, while based on Goal Programming, the total value is 93.18, and the total of procurement cost is IDR 32,621,000. PT GMT has been able to determine the optimal supplier based on the policies set.